Code name hélène eaudiobook A novel. - Lawhon, Ariel (Random House Audio, 2020)
Based on the thrilling real-life story of a socialite spy and astonishing woman who killed a Nazi with her bare hands and went on to become one of the most decorated women in WWII — from the New York Times bestselling author of I Was Anastasia and The Frozen River. "Will fascinate readers of World War II history and thrill fans of fierce, brash, independent women." —Lisa Wingate, #1 New York Times bestselling author of Before We Were Yours Told in interweaving timelines organized around the four code names Nancy used during the war, Code Name Hélène is a spellbinding and moving story of enduring love, remarkable sacrifice and unfaltering resolve that chronicles the true exploits of a woman who deserves to be a household name. It is 1936 and Nancy Wake is an intrepid Australian expat living in Paris who has bluffed her way into a reporting job for Hearst newspaper when she meets the wealthy French industrialist Henri Fiocca. No sooner does Henri sweep Nancy off her feet and convince her to become Mrs. Fiocca than the Germans invade France and she takes yet another name: a code name. As Lucienne Carlier, Nancy smuggles people and documents across the border. Her success and her remarkable ability to evade capture  earns her the nickname The White Mouse from the Gestapo. With a five million franc bounty on her head, Nancy is forced to escape France and leave Henri behind. When she enters training with the Special Operations Executives in Britain, her new comrades are instructed to call her Helene. And finally, with mission in hand, Nancy is airdropped back into France as the deadly Madam Andree, where she claims her place as one of the most powerful leaders in the French Resistance, armed with a ferocious wit, her signature red lipstick, and the ability to summon weapons straight from the Allied Forces. But no one can protect Nancy if the enemy finds out these four women are one and the same, and the closer to liberation France gets, the more exposed she — and the people she loves — become. Don't miss Ariel Lawhon's new book, The Frozen River!